Can head sway patterns differentiate between patients with Meniere’s disease vs. peripheral vestibular hypofunction? - Kelly, Jennifer L.; Cosetti, Maura; Lubetzky, Anat V. (Frontiers in Neurology, 2024)
Background Meniere’s disease (MD) is defined by episodic vertigo, unilateral sensorineural hearing loss and fluctuating aural symptoms. Due to the variable clinical presentation, objective tests of MD may have significant diagnostic utility. Head kinematics derived from a head-mounted display (HMD) have demonstrated to be sensitive to vestibular dysfunction. The purpose of this pilot study was to investigate whether head sway can differentiate between patients with MD, vestibular hypofunction (VH) and healthy controls. Materials/methods 80 adults (30 healthy controls, 32 with VH, and 18 with MD) were recruited from a tertiary vestibular clinic. All underwent a postural control assessment using the HTC Vive Pro Eye HMD that recorded head sway in the anterior–posterior (AP), medio-lateral (ML), pitch, yaw and roll direction. Participants were tested with 2 levels of visual load: a static versus oscillating star display. Each scene lasted 60 s and was repeated twice. Sway in each direction was quantified using root mean square velocity (VRMS) for the first 20 s and full 60 s of each scene. Results Static visual: participants with VH showed significantly larger head VRMS than controls in the AP (60 s and 20 s) and pitch (20 s) directions. Dynamic visual: participants with VH showed significantly larger head VRMS than controls all directions for both the 60 and 20 s analysis. Participants with MD did not differ significantly from the control or the VH group. Conclusion While limited in numbers, Patients with MD had a high variability in head sway in all directions, and their average head sway was between controls and those with VH. A larger sample as well as patients with worse symptoms at time of testing could elucidate whether head sway via HMD could become a viable test in this population. A similar finding between 20- and 60-s scene and the full portability of the system with an in-clinic testing setup could help these future endeavors. Head sway derived from HMD is sensitive to VH and can be clinically useful as an outcome measure to evaluate sensory integration for postural control.